The Effect of Resistance Exercise on Inflammatory and Myogenic Markers in Patients with Chronic Kidney Disease - Watson, Emma L.; Viana, Joao L.; Wimbury, David; Martin, Naomi; Greening, Neil J.; Barratt, Jonathan; Smith, Alice C. (Frontiers in Physiology, 2017)
Background: Muscle wasting is a common complication of Chronic Kidney Disease (CKD) and is clinically important given its strong association with morbidity and mortality in many other chronic conditions. Exercise provides physiological benefits for CKD patients, however the molecular response to exercise remains to be fully determined. We investigated the inflammatory and molecular response to resistance exercise before and after training in these patients. Methods: This is a secondary analysis of a randomized trial that investigated the effect of 8-week progressive resistance training on muscle mass and strength compared to non-exercising controls. A sub-set of the cohort consented to vastus lateralis skeletal muscle biopsies (n=10 exercise, n=7 control) in which the inflammatory response (IL-6, IL-15, MCP-1 TNF-), myogenic (MyoD, myogenin, myostatin), anabolic (P-Akt, P-eEf2) and catabolic events (MuRF-1, MAFbx, 14kDa, ubiquitin conjugates) and overall levels of oxidative stress have been studied. Results: A large inflammatory response to unaccustomed exercise was seen with IL-6, MCP-1 and TNF- all significantly elevated from baseline by 53-fold (P<0.001), 25-fold (P<0.001), and 4-fold (P<0.001) respectively. This response was reduced following training with IL-6, MCP-1 and TNF- elevated non-significantly by 2-fold (P=0.46), 2.4-fold (P=0.19) and 2.5-fold( (P=0.06) respectively. In the untrained condition, an acute bout of resistance exercise did not result in increased phosphorylation of Akt (P=0.84), but this was restored following training (P=0.01). Neither unaccustomed nor accustomed exercise resulted in a change in myogenin or MyoD mRNA expression (P=0.88, P=0.90 respectively). There was no evidence that resistance exercise training created a prolonged oxidative stress response within the muscle, or increased catabolism. Conclusions: Unaccustomed exercise creates a large inflammatory response within the muscle, which is no longer present following a period of training. This indicates that resistance exercise does not provoke a detrimental on-going inflammatory response within the muscle.